Routledge philosophy guidebook to Heidegger and Being and time - Mulhall, Stephen, 1962- (Routledge philosophy guidebooks., 1996)
"Heidegger is one of the most controversial thinkers of the twentieth century. His writing are notoriously difficult; they both require and reward careful reading. Being and Time, his first major publication, remains to this day his most influential work." "Heidegger and Being and Time introduces and assesses Heidegger's life and the background to Being and Time, the ideas and text of Being and Time, and Heidegger's continuing importance to philosophy and his contribution to the intellectual life of our century." "Ideal for anyone coming to Heidegger for the first time, this guide will be vital for all students of Heidegger in philosophy and cultural theory."--Jacket